Preparedness to maritime chemical accidents in the Baltic Sea region - Johanna Yliskylä-Peuralahti (ChemSAR project, Centre for Maritime Studies, University of Turku, 2022)
Despite the lack of common procedures and processes, countries of the Baltic Sea region have had a clear need to prepare for potential incidents nationally in their own territory. However, nationally coordinated practices, training and response measures differ between states due to no internationally coordinated preparations of common practices. ChemSAR aims at answering to this existing international need by producing common operational plans and operating procedures for search and rescue (SAR) operations involving HNS incidents where threat to human life is imminent. Operational plans and procedures are created in order to assure the execution of maritime SAR operations involving actors from several states in the Baltic Sea region. On the other hand, operational plans and procedures will be developed in a way that they are applicable in national context as well.
This background report lays out important information on the current situation and development needs. According to the survey, several authorities experience that there is a clear need for joint operational plans and procedures. Indeed, international cooperation is seen as a driving force in the ChemSAR project as well. The challenges posed in this report will be addressed in the development of the operational plans and procedures, yet the practical experiences from different exercises and testing phases will indicate the actual results of the work done.